MANAGING CONTENTION AVOIDANCE AND MAXIMIZING THROUGHPUT IN OBS NETWORK - AMIT KUMAR GARG (Journal of Engineering Science and Technology, 2013)
Optical Burst Switching (OBS) is a promising technology for future optical networks. Due to its less complicated implementation using current optical and electrical components, OBS is seen as the first step towards the future Optical Packet Switching (OPS). In OBS, a key problem is to schedule bursts on wavelength channels whose bandwidth may become fragmented with the so-called void (or idle) intervals with both fast and bandwidth efficient algorithms so as to reduce burst loss. In this paper, a new scheme has been proposed to improve the throughput and to avoid the contention in the OBS network. The proposed scheme offers the same node complexity as that in general OBS networks with optical buffers. Also, it avoids burst blockings in transit nodes, turning it into an efficient and simple burst contention avoidance mechanism. Simulation results show that the proposed scheme has improvement of 15% in terms of burst loss probability as compared to OBS existing schemes and also maximizes the throughput of the network without deteriorating excessively other parameters such as end to end delay or ingress queues.